The effect of employee performance through job satisfaction: work motivation and leadership at Satpol PP Padang Sidempuan North Sumatra - Arbiuddin Syahputra Hakim Harahap; Hapzi Ali; Lusiana Lusiana (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Human resources (HR) have an important role in the success of a business or organisation through their effort, talent, innovation, drive, and actual tasks. The purpose of this study is to analyse and reveal the effect of work motivation and leadership on job satisfaction and the effect of work motivation, leadership and job satisfaction on employee performance, the effect of organisational culture on employee performance at Satpol PP Padang Sidempuan North Sumatra. Then the effect of work motivation on employee performance mediated by job satisfaction, the effect of leadership on employee performance mediated by job satisfaction and the effect of communication on employee performance mediated by job satisfaction. The research method used is descriptive quantitative. The research was conducted with a sample size of 199 employees, data testing using SEM PLS. The results of this study indicate that there is an effect of work motivation, leadership, communication and job satisfaction partially on employee performance at Satpol PP Padang Sidempuan North Sumatra. The implications of the study found that there is no positive and significant effect of work motivation on job satisfaction and leadership and communication partially on job satisfaction.